The Application of technology in the english teaching learning process at the foreign language epartments of five universities in El Salvador - Barrera Cañada, Jhoanna Verónica; Cativo Alonzo, Astrid Lissette; Cortez Lozano, Gabriela Zaé; Gálvez Velásquez, Beatriz Elena; Guzmán Ruano, Morena Guadalupe (2024)
At the present time, the world of technology has changed vertiginously in such a way that the technological resources are everywhere in society, and education is not exempted from these advances. Due to the accelerated innovations that technology has had in computer science, telecommunication, and multimedia, it has a great impact in all human activities especially in education, in which new strategies for teaching – learning process have emerged. Therefore, technology brings great challenges as well as it opens interesting possibilities for education as Tickton (1970) states in Priscilla Norton’s book that “ In 1970 the commission of instructional technology confirmed its conviction that technology can make education more productive, more individual, and powerful, make learning more scientific based and make access to education equal”. Moreover, the use of technological advances in education, specifically in language teaching, has experienced an extraordinary development in the last two decades, as a consequence of the globalization phenomena which demands such requirements in the Education field, it does not mean that technology can do everything, but it makes things easier. Thus, El Salvador is not the exception of using technology in education, and in the case of higher education, teaching a second language is being assisted by technology somehow. At this time, to learn a foreign language is very important, and if while learning a second language technology is applied throughout the whole process, of course, there are going to be better results as Beauvois et al. from Stepp-Greany’s web site.(2002) stated: “The use of technology in foreign language learning also appears to influence the development of linguistic skills, several researchers have reported an improvement in student writing skills through the use of networked computers”; subsequently, technology has already gained an important place in the language classroom as a valuable and necessary tool; for that reason, its use is not a luxury, but a need.